"Alice in Wonderland syndrome" associated with topiramate for migraine prevention. Issue 2 (22nd June 2010) - Jürgens, T P; Ihle, K; Stork, J-H; May, A
Abstract : Various visual and sensory phenomena have been described in migraine with aura. Among those, the "Alice in Wonderland" syndrome is defined as a distortion of the body image with the patient being aware of its unreal nature. Here, the case of a 17-year-old girl with migraine without aura who developed an 'Alice in Wonderland' syndrome repeatedly on topiramate treatment was presented and potential pathophysiological concepts were discussed.